Tanggung Jawab Pengurus Koperasi Dalam Menyelesaikan Tunggakan Anggota Di Koperasi Serviam Cabang Penfui Kota Kupang - Rosaliani Viona Koten; Aloysius Sukardan; Darius Mauritsius (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Savings and Loans Cooperatives generally provide services to ensure the welfare of their members and make it easier to fulfill their members' living needs. In accordance with the nature of loan cooperatives or credit cooperatives, the main aim of the operation of these cooperatives is as an alternative means of borrowing money or credit. The formulation of the problem in this research is: (1) What are the responsibilities of the cooperative management in settling members' arrears at KSP Serviam Penfui Branch? (2) What factors hinder the management's responsibility in settling arrears at KSP Serviam Penfui Branch? This research is a type of empirical legal research where the data is obtained directly from the research location. This research uses data collection techniques by means of interviews and literature study. The data collected is then analyzed and then presented in a qualitative descriptive manner. The results of this research show: (1) The responsibility of the management of the KSP Serviam Penfui Branch cooperative in settling arrears is to provide members with an extension of time if the member experiences total arrears. The extension of time given is a delay of 10 days, a warning will be given by telephone or a first warning letter will be sent. For members who have postponed 30 days, a home visit will be made or a second warning letter will be sent. Members who have delayed 40 days or more will be visited at home or sent a third warning letter, accompanied by threats and sanctions, and offered to reschedule loan payments. If all the steps above are not fulfilled, the management meeting will decide to take legal action. By taking action to resolve arrears, it is hoped that members will be more orderly in repaying loans. (2) The factors causing arrears in service cooperatives are as follows: Weak supervisory system for cooperative management, lack of coordination between departments, lack of accuracy in analyzing credit provision, financial conditions of members, due to natural disasters, and business failure.